PENERAPAN PASAL 385 AYAT 4 KITAB UNDANG-UNDANG HUKUM ACARA PIDANA PADA PUTUSAN NOMOR 346 Pid.B/2011/Pn.Pbr DILIHAT DARI KONSEP KEPEMILIKAN TANAH MENURUT HUKUM ADAT - Hendra, Rahmad; ', Margain; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Prior to the enactment of the law the land sector in Indonesia, the applicable rules of customary law, as is also recognized in Article 5 of Law No. 5 of 1960 on the Basic Regulation of Agrarian. On that basis, the status of land ownership in Indonesia is not necessarily seen by the formal proof in the form of a letter or deed their land as intended by the Act Agrarian land ownership on the basis of customary law is still recognized. This dualism resulting in disputes about the status of land ownership in practice.As for the purpose of writing this paper is to investigate the application of criminal law article 385 paragraph 4 of the rules of evidence as stipulated in the law on criminal procedure and to determine the legal considerations of the judges in the decision on the criminal case No. 346 / Pid.B / 2011 / PN.PBR seen from the concept of land ownership under customary law.This type of research is a normative legal research in the form of studies document / case, because the research conducted by Docket No. 346 / Pid.B / 2011 / PN.PBR, in conclusion, the author uses the inductive method is by way of drawing conclusions from things Special character (from the data obtained from the study) the provisions of general law.In application of Article 385 paragraph 4 of scams there are elements which would conflict with land ownership customary law because the legal concept of land in Indonesia that adheres stelsel negative berunsurkan positive segingga the right base of the country does not ensure the full ownership of the land, meaning there's still other evidence such as physical evidence and other evidence and can be used as guidelines for judges in sentencing for this article related to land ownership. The judges' verdict likely to be taken in terms of formality so that it will ignore the sense of justice in the society where judges regarded as most people know the lawKeywords: Application - Fraud - Land Owners - Indigenous